KENDALA PERLINDUNGAN HUKUM TERHADAP BURUH MIGRAN DI KABUPATEN CILACAP - TriLisiani Prihatinah; Noor Asyik; Kartono Kartono (Jurnal Dinamika Hukum, 2012)
In Cilacap, migrant workers are the second largest contributors of foreign exchange after oil and gas sector. It's just the contribution of migrant workers is not consistent with the protection provided by the government, seen by the increasing cases of abuse, sexual violence and trafficking. This research located in Cilacap District using normative-sociological approach to analyze the problems of migrant workers in the normative and empirical levels. The results showed that the normative provisions at the national level have not been able to reach the whole problematics of service and protection of migrant workers in the District. The normative problems include the overlapping of the regulation, duplication of regulation, and provision multiple interpretations that complicate its application. Legislation in general is also not reaching abuses of administration officials. While the results of an empirical study illustrate that the complaints of violence against migrant workers conducted largely by parents and migrant workers are mostly from poor families. Key words: migrant workers, protection, local regulation